CODE SWITCHING IN "SUNNY AND CHRIS" YOUTUBE CHANNEL - Citra, Dewi; Abdullah, Abdullah; Sunra, La (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
A bilingual or multilingual has the ability to switch their language, they can do variations of language in one discourse, this case is called code switching. The main things analyzed in this research is about the types of Code-Switching in Sunny and Chris YouTube Channel. In this research, the researcher uses a qualitative analysis method that focuses on collecting, organizing and identifying the types of Code-Switching in several selected videos on the Sunny and Chris YouTube Channel. All types of Code-Switching based on Poplack’s theory were found in the selected videos by the researcher as a outcome of this research. They are extra-sentential Code-Switching, inter-sentential Code-Switching, intra-sentential Code-Switching. And the most commonly found type is intra-sentential Code-Switching.